1998
DOI: 10.2989/025776198784127024
|View full text |Cite
|
Sign up to set email alerts
|

Comparing trophic flows in the southern Benguela to those in other upwelling ecosystems

Abstract: A balanced trophic flow model of the southern Benguela ecosystem is presented, averaging the period 1980-1989 and emphasizing upper trophic levels. The model is based largely on studies conducted within the framework of the Benguela Ecology Programme and updates the results of an expert workshop held in Cape Town in September 1989. Small pelagic fish other than anchovy Engraulis capensis and sardine Sardinops sagax, mainly round herring Etrumeus whiteheadi and mesopelagic fish, were important components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 28 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…Another factor that could have biased the observed trend in TL m is the relatively low trophic level of small pelagic fish in Central Chile (TL=2.02) compared to TLs of similar species in comparative ecosystems (Jarre-Teichmann et al, 1998). The low TL of small pelagic fish in Central Chile is explained by the fact that, in this system, unlike other upwelling systems, these species seem to feed almost exclusively on phytoplankton (Arrizaga, 1983;Arrizaga et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Another factor that could have biased the observed trend in TL m is the relatively low trophic level of small pelagic fish in Central Chile (TL=2.02) compared to TLs of similar species in comparative ecosystems (Jarre-Teichmann et al, 1998). The low TL of small pelagic fish in Central Chile is explained by the fact that, in this system, unlike other upwelling systems, these species seem to feed almost exclusively on phytoplankton (Arrizaga, 1983;Arrizaga et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Food-web models using the Ecopath with Ecosim approach were also used in the region for describing within-system structural changes over time (Heymans et al 2004, Watermeyer et al 2008a or for comparisons with other ecosystems (Jarre-Teichmann et al 1998, Shannon et al 2008, 2009). These modeling studies (e.g., Shannon et al 2009) have suggested that the energy flows within ecosystems can be disrupted by changes in the abundance of small pelagic fishes.…”
Section: The Role Of Small Pelagic Fishes and What Canmentioning
confidence: 99%
“…The modelling approach used was ECOPATH with ECOSIM (EwE; Pauly 1992, Walters et al 1997). Local scientists and international experts at the workshop agreed on how the structure of existing ECO-PATH models of the region (Jarre-Teichmann et al 1998, Shannon andJarre-Teichmann 1999) should be modified in order to tailor the model to the fishing scenarios to be tested. The major product of this phase of the project was an updated ECOPATH model that described trophic flows in the northern Benguela in the late 1990s, following the anomalous environmental conditions experienced during 1994 and early 1995 (Roux and Shannon 2000).…”
Section: Ecosystem Model Of the Northern Benguelamentioning
confidence: 99%